Partitioning of trace metals in the chemical fractions of bed-load sediments of Nahr-Ibrahim river, Lebanon - Korfali, Samira I. (1999)
Full text.Sediments are the ultimate sink of trace elements. The total metal analysis may only give information concerning possible enrichment of metals. The analysis of metal partitioning in the different chemical components of sediments (exchangeable, carbonate, easily reducible, moderately reducible, organic and residual); give a detailed information on the way in which these metals are bound to sediments, their mobilization capacity and their ability to affect water quality under different environmental conditions. The studied river basin is dominated by limestone formation, the enrichment of metals in the carbonate sediment fraction is a high probability. The objective of the study was to determine the percentage of the total metal content (Fe, Mn, Zn, Cu and Pb) in the six chemical fractions of the bed load sediments of Nahr-Ibrahim river during the dry season and verify the role of carbonate for metal sediment deposition. Bed load sediments were sampled at five locations 13Km stretch, upstream from river mouth at two dates, August and October 1996. the dried samples were sieved into three mechanical fractions (1180-250 μm, 250-75 μm and <75 μm). A sequential chemical extraction was carried on each sized sample sediment, Fe, Mn, Zn, Cu and Pb were determined on the extracts by AAS. The reported data showed that Fe in mainly in the residual fraction, Mn in the residual and carbonate fraction, Zn in the residual, carbonate and Fe oxide fraction, Cu in the residual, carbonate and organic fraction, Pb in the carbonate fraction. The carbonate fraction in sediments played the major common role for metal sediment deposition